2020
DOI: 10.1101/2020.03.02.972612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early-life social experience shapes social avoidance reactions in larval zebrafish

Abstract: Highlights:• Larval zebrafish raised in isolation show enhanced social avoidance reactions • Enhanced avoidance is composed of increased avoidance distances and usage of high acceleration escape swims• The lateral line sensory organ is necessary and sufficient for the increased usage of high acceleration escape swims Summary Social experiences greatly define successive social behavior. Lack of such experiences, especially during critical phases of development, can severely impede the ability to behave adequate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 80 publications
3
6
0
Order By: Relevance
“…Interestingly, a similar finding has been made in socially isolated zebrafish larvae. When exposed to a social interaction, these larvae show enhanced social avoidance using high‐acceleration escape swim bouts and a short latency C‐start to escape from the situation, 60 similar to our data. At larval stages, hrh3 expression is strongest in the telencephalon, 25 indicating that this area may mediate the observed phenotypic differences.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, a similar finding has been made in socially isolated zebrafish larvae. When exposed to a social interaction, these larvae show enhanced social avoidance using high‐acceleration escape swim bouts and a short latency C‐start to escape from the situation, 60 similar to our data. At larval stages, hrh3 expression is strongest in the telencephalon, 25 indicating that this area may mediate the observed phenotypic differences.…”
Section: Discussionsupporting
confidence: 90%
“…Larval zebrafish are known to alter their behaviour in response to an acute stressor (De Marco et al, 2013Lopez-Luna et al, 2017;Lee et al, 2019) and following exposure to a physical stimulus (Castillo-Ramírez et al, 2019). Zebrafish larvae display a variety of behaviours that can be quantified (Kalueff et al, 2013;De Marco et al, 2014Groneberg et al, 2015;Karpenko et al, 2020) and exhibit social behaviour (Engeszer et al, 2007;Dreosti et al, 2015;Groneberg et al, 2020), some of which can be modulated by stressor exposure (Eachus et al, 2017;Shen et al, 2020). In the adult zebrafish, a wide variety of behavioural paradigms have been established including tests for anxiety (Egan et al, 2009;Maximino et al, 2010;Stewart et al, 2012), social behaviour (Green et al, 2012;Carreño Gutiérrez et al, 2019), fear (Faustino et al, 2017), and aggression (Oliveira et al, 2011;Carreño Gutiérrez et al, 2018).…”
Section: The Stress Response In Zebrafishmentioning
confidence: 99%
“…In nature, zebrafish aggregate and form social groups, called “shoals.” The dynamics of this group forming behavior is highly complex and debated to this day. Numerous environmental factors play roles in shoal formation, including vegetation, water flow speed, temperature, age of the fish, geographical location, existing shoal size, predation, early life experience, and food availability, to name a few (Ruhl and McRobert, 2005 ; Miller and Gerlai, 2007 , 2011 ; Arganda et al, 2012 ; Suriyampola et al, 2016 ; Orger and de Polavieja, 2017 ; Groneberg et al, 2020 ). For example, zebrafish in still waters are more likely to form smaller shoals compared to fast-moving water, where shoals of upwards of 300 individuals have been observed (Suriyampola et al, 2016 ).…”
Section: Zebrafish Shoaling Behaviormentioning
confidence: 99%
“…A social preference experiment by Engeszer et al ( 2004 ) demonstrated that when striped wildtype (WT) zebrafish and non-striped nacre zebrafish (lacking stripes due to mutation in the mitfa gene) were reared either with their genotype or the opposite (WT raised with nacre and vice versa), the experimental fish preferred the phenotype they were reared with, regardless of their genotype. Lastly, zebrafish raised in complete social isolation were found to stay significantly further away from shoal mates and showed diminished social preference compared to zebrafish raised in normal social conditions, demonstrating that lack of access to social stimuli during early development leads to abnormal social response (Engeszer et al, 2004 ; Shams et al, 2018 ; Groneberg et al, 2020 ). Preliminary studies of our own also suggest that enriched social and/or physical environment may rescue embryonic alcohol exposure-induced social behavioral deficits in zebrafish.…”
Section: Zebrafish Shoaling Behaviormentioning
confidence: 99%
See 1 more Smart Citation